Education for civic and political participation : a critical approach - Hedtke, Reinhold; Zimenkova, Tatjana (New York : Routledge, 2013)
"Participation as an element of active citizenship in democracies is a key project of international and national educational policy. Institutionalized approaches for compulsory schools provide participatory access to all young European citizens. But does this picture depict the possibilities and practices of participation appropriately? Can this standard approach to participation be translated into action in view of diverse polities, policies, political cultures, institutions and practices of participation? This book explores what prerequisites must be given for a successful implementation of such a comprehensive international project"--
pt. I. Taken-for-grantedness and hidden normativity? : foundations and framings of participatory education policies -- pt. II. Ambitious policies, ambiguous practices? : approaches and impacts of participatory education in schools and beyond -- pt. III. Included by education, excluded by politics? : tensions, gaps and contradictions of participatory education -- pt. IV. Shadows of the pasts, privacies in the present? : tracing participatory education back to Soviet and authoritarian systems -- pt. V. Conclusion.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Citizenship -- Study and teaching -- Europe -- Cross-cultural studies; Democracy and education -- Europe -- Cross-cultural studies; Electronic books